Rice husk-derived hard carbons as high-performance anode materials for sodium-ion batteries. (February 2018) - Wang, Qiaoqiao; Zhu, Xiaoshu; Liu, Yuhan; Fang, Yuyan; Zhou, Xiaosi; Bao, Jianchun
Abstract: Sodium-ion batteries (SIBs) have drawn ever-increasing attention for scalable electrical energy storage owing to the inexhaustible sources and wide distribution of sodium. However, to develop feasible anode materials still remains a great challenge for the practical application of SIBs. Here, we report hard carbons derived from a plentiful and deserted biomass of rice husk through a facile acid treatment and subsequent pyrolysis. The investigation illustrates that the electrochemical properties of the rice husk-derived hard carbons (RHHCs) are significantly influenced by the pyrolysis temperature because of the discrepancy in their microstructure. The RHHC pyrolyzed at 1300 °C (RHHC-1300) shows the highest reversible capacity of 372 mAh g −1 and good cycling stability and rate performance due to its large interlayer distance and suitable oxygen content. Moreover, full sodium-ion batteries are assembled to examine the application prospect using Na3 V2 (PO4 )2 F3 /C and RHHC-1300 as cathode and anode materials, respectively, delivering a high-energy density of 185 Wh kg −1 and stable cycling performance. This work could intensify the fundamental understanding of the sodium storage mechanism in biomass-derived hard carbons. Graphical abstract: Image 1